MEMBANGUN PENGETAHUAN TEORI PERSAMAAN DIFERENSIAL TINGKAT I MELALUI TUGAS TERSTRUKTUR - Mudjiono; Sigit Setya Wiwaha; Aly Imron (Politeknik Negeri Malang, 2022)
The research aims to describe how the structured task needs to be formulated and the extent to which it has an impact on improving student achievement. This research is based on Vygotsky's view which states that the potential of students will develop effectively if in the learning carried out, external factors, especially teachers/lecturers and students' friends are involved in learning. Cooperative learning is a learning system that contains various interrelated elements, including: (1) positive interdependence, (2) faceto-face interaction, (3) individual accountability, and (4) skills to establish interpersonal relationships. Structured task-based learning as a form of cooperative learning consists of 4 principles, namely: (1) Making assignments meaningful, clear, and challenging, (2) Diversifying assignments, (3) Paying attention to the level of difficulty, (4) Monitoring student progress. The method in this study uses two approaches, namely a qualitative approach and a quantitative approach. The effect of the action on the group given the task was calculated through the statistical tool of analysis of variance. After two actions were taken, it was found that the students who were given the task got a higher academic score. The key is that on every assignment given, the lecturer needs to provide feedback, especially on difficult questions.